2003
DOI: 10.1002/cne.10667
|View full text |Cite
|
Sign up to set email alerts
|

GFAP knockout mice have increased levels of GDNF that protect striatal neurons from metabolic and excitotoxic insults

Abstract: In response to injury and degeneration, astrocytes hypertrophy, extend processes, and increase production of glial fibrillary acidic protein (GFAP), an intermediate filament protein located within their cytoplasm. The present study tested the hypothesis that GFAP expression alters the vulnerability of neurons to excitotoxic and metabolic insult induced by 3-nitroproprionic acid (3-NP), an irreversible inhibitor of mitochondrial complex II activity or the excitotoxin quinolinic acid (QA). In this respect, adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 50 publications
3
32
0
Order By: Relevance
“…In this regard, it is worth mentioning that, similar to the brain, GDNF expression in the adult carotid body, a neuronal crest-derived organ of the peripheral nervous system that contains high levels of this trophic factor (ToledoAral et al, 2003;Pardal et al, 2007), appears in neuron-like glomus cells rather than in the glia-like sustentacular type II cells (Villadiego et al, 2005). As reported before (Hanbury et al, 2003;Saavedra et al, 2008), striatal GDNF expression was upregulated in response to toxic injury of dopaminergic nigrostriatal neurons, but, surprisingly, this appeared to be a consequence of increased GDNF production in neurons rather than in glial cells. Although in MPTP-lesioned animals we observed a clear increase in the number of striatal astrocytes and microglia, evidence of GDNF-LacZ transcriptional activity was seen only in neurons.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…In this regard, it is worth mentioning that, similar to the brain, GDNF expression in the adult carotid body, a neuronal crest-derived organ of the peripheral nervous system that contains high levels of this trophic factor (ToledoAral et al, 2003;Pardal et al, 2007), appears in neuron-like glomus cells rather than in the glia-like sustentacular type II cells (Villadiego et al, 2005). As reported before (Hanbury et al, 2003;Saavedra et al, 2008), striatal GDNF expression was upregulated in response to toxic injury of dopaminergic nigrostriatal neurons, but, surprisingly, this appeared to be a consequence of increased GDNF production in neurons rather than in glial cells. Although in MPTP-lesioned animals we observed a clear increase in the number of striatal astrocytes and microglia, evidence of GDNF-LacZ transcriptional activity was seen only in neurons.…”
Section: Discussionmentioning
confidence: 69%
“…As it has been proposed that GDNF production increases upon brain damage (Hanbury et al, 2003), mainly due to upregulation of the GDNF gene in glial cells (Hughes et al, 1999;Bresjanac and Antauer, 2000;Saavedra et al, 2008), we studied GDNF expression in GDNF-LacZ animals treated with a single MPTP dose to induce partial or complete destruction of dopaminergic nigrostriatal neurons (Mejías et al, 2006). These animals, examined 7-21 d after MPTP injection, exhibited a characteristic strong striatal astroglial reaction (Figure 3 A, D).…”
Section: Gdnf Expression In Normal and Injured Adult Striatum Is Confmentioning
confidence: 99%
“…GDNF has been demonstrated to have neuroprotective and neurorestorative actions in primate models of PD and is currently being administered to PD patients in clinical trials (41)(42)(43)(44)(45). The concentrations of GDNF in the right and left CN of the CR monkeys were nearly 3-fold higher than levels measured in the same region of monkeys on the control diet (Fig.…”
Section: Resultsmentioning
confidence: 92%
“…Vitamin C has a wellknown antioxidant protective role (Loo et al 2003). The expression of GFAP was suggested to have neuroprotective effect after a neurotoxic or metabolic insult (Hanbury et al 2003). The use of male animals in the present study was attributed to the finding of Suárez et al (1992) who suggested an influence of circulating sex steroids on GFAP immunoexpression.…”
Section: Discussionmentioning
confidence: 89%
“…uptake was decreased maintaining extracellular glutamate at safe levels. The expression of GFAP was reported to play a key role in regulation of the extracellular glutamate levels and have neuroprotective effect after an excitotoxic or metabolic insult (Hanbury et al 2003;Hughes et al 2004). On the other hand, the decreases in GFAP expression and astrocyte dysfunction was reported to compromise neuronal survival and are associated with detrimental conditions in the CNS (Pekny and Pekna 2004;Giffard and Swanson 2005).…”
Section: Discussionmentioning
confidence: 98%